Micromagnetic Simulation of the Depinning Field Domain Wall on Symmetric Double Notch Ferromagnetic Wires - Djuhana, Dede; Supriyanto, Erwin; Kim, Dong Hyun (Makara Journal of Science, 2014)
In this paper, we investigate the depinning field domain wall on symmetric double notch ferromagnetic wires by means of micromagnetic simulation for Permalloy (Py), Cobalt (Co), and Nickel (Ni) materials. The depinning field domain wall increases as the size of the notch decreases. At a lower depinning field, the domain wall inner structure exhibited a transverse wall (TW), while at a higher depinning field, there was a transformation of the domain wall inner structure from transverse wall to antivortex wall (AVW). We also observed that the magnetization energy increased as the size of the notch decreased. This means that more energy was needed to release the domain wall from a smaller notch. Micromagnetic simulation showed that the depinning field domain wall depends on the size of the notch and on the ferromagnetic anisotropy.